Frozen section examination of sentinel lymph nodes can be used as a decisional tool in the surgical management of early cervical cancer. Issue 3 (6th January 2020) - Rychlik, Agnieszka; Angeles, Martina Aida; Migliorelli, Federico; Croce, Sabrina; Mery, Eliane; Martinez, Alejandra; Ferron, Gwenael; Guyon, Frederic; Querleu, Denis
Abstract : Introduction: Sentinel lymph node (SLN) detection has been shown to be accurate in detecting lymph node involvement in early-stage cervical cancer. The objective of this study was to evaluate the accuracy of frozen section examination in the assessment of SLN status, with the aim of adequately driving the intra-operative decision. Methods: We designed a retrospective study including patients from two comprehensive cancer centers between January 2001 and December 2018 with early-stage cervical cancer (IA1-IB2 according to International Federation of Gynecology and Obstetrics (FIGO) 2018) undergoing SLN dissection. The SLN procedure was performed using a cervical injection with technetium-99m combined with blue dye or indocyanine green in most cases. Results: A total of 176 patients fulfilled inclusion criteria. Bilateral mapping was detected in 153 (86.7%) of them. Nineteen of these patients (12.4%) had SLN involvement: 13 with macrometastases, three with micrometastases and three with isolated tumor cells (ITC). Macrometastatic disease was missed on frozen section in 3/13 FIGO 2018 stage IIIC patients. The three patients with ITC were also missed by frozen section examination. Considering only macrometastases as lymph node involvement, frozen section sensitivity was 76.9% (95% CI 49.7 to 91.8) and negative predictive value (NPV) was 97.9% (95% CI 94.0 to 99.3) in patients with bilateral detection. Including micrometastases, sensitivity was 81.2% (95% CI 57.0 to 93.4) and NPV remained at 97.9% (95% CI 93.9 to 99.3). Conclusions: With a prevalence of final-stage IIIC in patients with pre-operative early-stage cervical cancer of the order of 10% in this series, the NPV of frozen section examination of SLN is very high, with an inferior limit of the CI superior to 94%. Diagnostic accuracy remains acceptable even if micrometastases are considered. The impact of missed ITC has not been established. Frozen section examination can be incorporated in the intra-operative decision algorithm.